Editorial - Burkiewicz, Łukasz (Perspektywy Kultury, 2021)
The cover title of the new issue, An Oriental Journey, has attracted a great deal of interest from authors of various disciplines. Scholars of both remote and recent history have passionately explored this theme. The issue section contains three articles related to the medieval Levant. Wojciech Mruk, a medievalist from the Jagiellonian University, analyses the account given by Lionardo Frescobaldi, Simone Sigoli and Giorgio Gucci, who made a peregrination to the Holy Land together between 1384 and 1385. Another article, by Christopher Schabel (Cyprus University in Nicosia), discusses the best-known medieval Cypriot village of Psimolofu and its links with the patriarchs of Jerusalem. Nicholas Coureas of the Cyprus Research Center provides a broad perspective on the presence of the Greek Church on Cyprus during the Lusignan and Venetian rule (1191–1571). The next contribution takes us back to the 20th century and even further to the East. Magdalena Filipczuk (Jesuit University Ignatianum in Krakow) reconstructs selected themes in the reflections by Lin Yutang, a Chinese thinker, translator and editor, based on his work towards explaining and popularizing Chinese culture and philosophy in the West. One more article that takes us to the Far East, but back in time, is by Małgorzata Sobczyk (Nicolaus Copernicus University in Toruń) undertakes to characterize the image of a Japanese woman in the light of sixteenth-century European accounts. The next three studies invite us to learn more about Poles and their presence in the East. Ewa Siemieniec-Gołaś (Jagiellonian University) makes an attempt to discuss the figure of Władysław Jabłonowski, not only a physician in the Ottoman service, but also an expert and researcher of the East. Beata Gontarz (University of Silesia in Katowice) discusses the cultural experience of Jan Józef Szczepański based on his book Do raju i z powrotem [To Paradise and Back]. The last article in the issue section is a work of turkologist Sylwia Filipowska (Jagiellonian University), who discusses the circumstances of Tadeusz Kowalski’s journey to Turkey in 1927.